Behavioral Strong Implementation - Takashi Hayashi; Ritesh Jain; Ville Korpela; Michele Lombardi (Aboa Centre for Economics (ACE), 2021)
Choice behavior is rational if it is based on the maximization of some context-independent preference relation. This study re-examines the questions of implementation theory in a setting where players' choice behavior need not be rational and coalition formation must be taken into account. Our model implies that with boundedly rational players, the formation of groups greatly affects the design exercise. As a by-product, we also propose a notion of behavioral efficiency and we compare it with existing notions.
Keywords: D11; D60; D83; 330; Strong equilibrium; implementation; state-contingent choice rules; bounded rationality